SISTEM INFORMASI GEOGRAFIS TEMPAT PENDIDIKAN AL-QUR’AN DI KABUPATEN SUKOHARJO - Risal Eko Nugroho (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2019)
There are 45 location of Al-Qur'an education in Sukoharjo Regency, The people in Sukoharjo are currently searching for location of Al-Qur'an educati by asking questions from informants and looking at pamphlets at the public space. The aims of this study is to make the geographic information system of Al-Our'an education location in Sukoharjo Regency. Therefore, it makes easier for people to find the location of the Al-Qur'an educational. Geographical information system of Al-Qur'an education location in Sukoharjo Regency used data collection methods by observing, interviewing, and literature reviewing. The system development method used waterfall method. Whereas, the system testing method used black-box testing and questionnaire testing. The results of testing system using black-box testing from 2 test cases with 14 detailed testing can be concluded that the system works as expected. On the results testing of visitor satisfaction questionnaire, the average calculation of the overall scores using the Likert Scale obtained 45.5 % respondents states strongly agree and 41% states Agree. Therefore, it can be concluded that all visitors accept this system.